Neurobiological basis of autism spectrum disorder: mini review - Holanda, Maria Vanessa Freitas; Paiva, Eva da Silva; de Souza, Larissa Nayara; Paiva, Karina Maia; Oliveira, Rodrigo Freire; Tavares, Élyssa Adriolly Freitas; Morais, Paulo Leonardo Araújo de Góis; de Andrade, Ariel Moraes; Knackfuss, Maria Irany; do Nascimento, Ellany Gurgel Cosme; Cavalcanti, José Rodolfo Lopes de Paiva (Frontiers in Psychology, 2025)
Autism Spectrum Disorder is a neuropsychiatric condition characterized by deficits in communication, social interaction, and repetitive behaviors, with significant symptom variability. This multifaceted profile reflects a complex genetic architecture as well as diversity in morphological characteristics. Therefore, the objective of this review is to discuss the genetic and morphological aspects that may contribute to understanding autism. No temporal restrictions were applied for study inclusion, nor were there limitations regarding language. Scientific articles available in full text and directly related to the topic were included, while editorials, letters, conference abstracts, theses, dissertations, and books were excluded. The results of this review converge on two main aspects: (1) genetic and morphological findings are essential for a more comprehensive understanding of the disorder, providing an important basis for investigating its underlying mechanisms; and (2) despite their relevance, the results are still incipient and insufficient to explain the full clinical and behavioral heterogeneity associated with autism, highlighting the need for further studies.